Pharmacological Evaluation Of Garcinia Kola Nuts For Anti-Trichomonal Activity - GABRIEL. F IBIKUNLE; EMMANUEL O. OGBADOYI (International Journal of Pharma and Bio Sciences, 2011)
Treatment options for trichomoniasis are extremely limited. Newer drugs are therefore needed. Antitrichomonal effects of G. kola nuts were evaluated so that extracts with significant antitrichomonal activities can be standardized for use in phytotherapy of trichomoniasis. Powdered nuts were extracted with 100% methanol (A) and 50% methanol (B). The marc from A was further extracted in water to obtain (C). A, B, C, and fractions of A were screened against Trichomonas gallinarum in vitro. Antitrichomonal activities were in the order A> B > C at 24 h with LC50 and LC90 of 36.14., 50.12, 212.9 and 293.77, 535.29, 5355.4 (µg/ml) respectively. At 48 h, the order was B> A > C with LC50 and LC90 of 58.51, 139.55, 195.62 and 195.62, 1434.09 and 2887.29 (µg/ml) respectively. It is concluded that these extracts are sufficiently trichomonacidal and therefore potentially useful as therapeutic agents in the control of trichomoniasis.